3 - L'agriculture traditionnelle itinérante comme menace de l'environnement forestier: Quelles solutions - Seka, Pierre Roche (Africa Development, 1998)
Agriculture remains the main economic activity in Côte d'Ivoire. However, the traditional fanning techniques of bush burning jeopardise the very perenniality of the forest. The fundamental issue is, therefore, how to use it rationally in order to maximise the agricultural potential without impairing the eco-system as well as the well-being of the Ivorian peasant. This article shows that indiscriminate depletion of forest resources stems from the misconception that, in the mind of the peasant, only virgin forest is arable land. In order to check the mad rush for this limited forest resource, the author believes that a land tax should be levied with a view to ensuring a more rational use of the spaces already occupied; thus compelling the peasants to turn the abandoned fallows into fanning plots. Moreover, as an incentive, an experimentation programme aimed at comparing production on a non-treated forest area with production on a treated fallow area, is proposed as well.